Exploring the Relationship Between Broken Homes and Mathematical Literacy: A Quantitative Study of Junior Secondary School Students - Akorede Asanre; Aviwe Sondlo; Taiwo Abiodun (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examined the impact of broken homes (family conflicts, substance abuse, and single-parent households) on Junior secondary school students' mathematical performance in Abeokuta North Local Government Area, Ogun State, Nigeria. A survey research design using a quantitative approach was used, and a convenient sampling technique guided the selection of 5 schools from the population, of which 300 students were selected using simple random sampling. Four research questions guided this study. Broken Homes Questionnaire and Mathematics Academic Performance Test (MAPT) with reliability coefficients of 0.73 and 0.68, respectively, were used. The data were analyzed using regression analysis and descriptive statistics. Findings reveal no impact of family conflict, but substance abuse and single-parent households show a great impact on junior secondary school learners' performance in mathematics. Lastly, the results also show that the joint impact of the three variables has a great influence on the children's performance in school. In conclusion, single parenting, substance abuse, and family conflicts have an adverse effect on learners' academic performance. This is clearly linked to the looking-glass theory, emphasizing that a child will become what he experienced at home, which will, in turn, after the academic career. It is recommended that students from broken homes should be properly monitored, secured, and controlled